The Unit Auxiliary Transformer Analysis By Dissolve Gas Analysis and Breakdown Voltage Test - Ali, Muhamad; Fahreza, Firdha Khriska (Jurnal Edukasi Elektro, 2024)
The unit auxiliary transformer (UAT) is critical equipment at the Adipala steam power plant. Failure of this device can cause severe disruption to the generator, which can impact the Java-Bali electric power system. For this reason, the auxiliary transformer needs to be adequately maintained to ensure the equipment is in good condition. This article will discuss predictive maintenance efforts on UAT, including various inspections and tests on transformer oil to ensure the equipment can work properly. The research method includes carrying out various tests on the condition of transformer oil. The testing process involves taking samples of transformer oil, measuring the dissolved gas content, and testing the breakdown voltage in the laboratory. Data analysis using descriptive statistics referring to IEEE C57.104-2019 and IEC 60422-2013 standards. The test results showed that the oil condition increased the amount of dissolved gas beyond the permitted limit. Therefore, it is necessary to monitor oil conditions and temperature to ensure the UAT can work correctly.